2014
DOI: 10.1021/ct500218p
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Calculations for the Peripheral Binding of Proteins/Peptides to an Anionic Membrane. 1. Implicit Membrane Models

Abstract: The binding of peptides and proteins to the surface of complex lipid membranes is important in many biological processes such as cell signaling and membrane remodeling. Computational studies can aid experiments by identifying physical interactions and structural motifs that determine the binding affinity and specificity. However, previous studies focused on either qualitative behaviors of protein/membrane interactions or the binding affinity of small peptides. Motivated by this observation, we set out to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 102 publications
1
44
0
Order By: Relevance
“…Similar to our previous observations, the vertical differential solvation free energies (ΔΔ W slv ) of RecA binding to the membrane correlate with Δ F bind and overestimate this parameter (Zhang et al, 2014). The calculated binding affinity for the parallel binding conformation of RecA to the membrane is substantially stronger than the perpendicular mode by ~5 kcal/mol.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to our previous observations, the vertical differential solvation free energies (ΔΔ W slv ) of RecA binding to the membrane correlate with Δ F bind and overestimate this parameter (Zhang et al, 2014). The calculated binding affinity for the parallel binding conformation of RecA to the membrane is substantially stronger than the perpendicular mode by ~5 kcal/mol.…”
Section: Resultssupporting
confidence: 88%
“…We computed the binding free energies of the two binding conformations using the GBSW-GCS model and the thermodynamic cycle described recently (Zhang et al, 2014), which demonstrated that this methodology accurately predicts the binding free energy of peptides with membranes. We tested several mutants that were designed based on the observed RecA/membrane binding interface, which involves mainly the DNA binding loop L2 and the N-terminal helix; to a lesser extent, the C-terminal domain also contributes to binding in the parallel binding conformation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phe residues, due to their elevated hydrophobicity, are found closer to the bilayer center (magenta curve) at ~± 12 Å. Implicit membrane simulations by Zhang, Yetiraj and Cui [38] likewise report this trend for the MARCKS-ED peptide where the charged and polar residues are found in the high dielectric constant region and the Phe residues are found close to the dielectric boundary. In comparison to Ellena et al [18] ~5-10 Å below the lipid phosphate was where they observed the Phe residues in the presence of Phosphatidylinositol 4,5-bisphosphate (PIP 2 ).…”
Section: Resultsmentioning
confidence: 75%